Abandonment and isolation of Fistula Clients by spouses / partner and society - Malungo, Jacob; Kasanda, Goshon; Mijere, Jenipher (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: The study investigated the extent to which women who had experienced fistula had been Ostracized or abandoned by spouses or partners. Methods: Descriptive study Results: Thirty-eighty per cent ((38) of the fistula victims were abandoned by their husbands or partners while sixty-two percent (62%) were not. Fifty percent of those abandoned had no living children. This percent decreased with increasing number of children. The breakup in the marriage was more reported among spouses who did not have any living children. There were utterances to the effect that where divorce had not occurred, the men had married additional women or co-wives for them to enhance sexual intercourse and bear children. Spouses who did not abandon their wives fully took responsibility in taking care of them, including giving them medical and economic support. Conclusions: There is marital break-up more on those who have not children. The family members took responsibility of those who had been abandoned by their spouses.